Atypical Genotypes for Canine Agouti Signaling Protein Suggest Novel Chromosomal Rearrangement - Dreger, Dayna L. (Genes (Basel), 2020)
Canine coat color is a readily observed phenotype of great interest to dog enthusiasts; it is also an excellent avenue to explore the mechanisms of genetics and inheritance. As such, multiple commercial testing laboratories include basic color alleles in their popular screening panels, allowing for the creation of genotyped datasets at a scale not before appreciated in canine genetic research. These vast datasets have revealed rare genotype anomalies that encourage further exploration of color and pattern inheritance. We previously reported the simultaneous presence of greater than two allele variants at the Agouti Signaling Protein (ASIP) locus in a commercial genotype cohort of 11,790 canids. Here we present additional data to characterize the occurrence of anomalous ASIP genotypes. We document the detection of combinations of three or four ASIP allele variants in 17 dog breeds and Dingoes, at within-breed frequencies of 1.32–63.34%. We analyze the potential impact on phenotype that these allele combinations present, and propose mechanisms that could account for the findings, including: gene recombination, duplication, and incorrect causal variant identification. These findings speak to the accuracy of industry-wide protocols for commercial ASIP genotyping and imply that ASIP should be analyzed via haplotype, rather than using only the existing allele hierarchy, in the future.